PENGARUH KONSEP DIRI DAN SELF EFFICACY MAHASISWA JURUSAN AKUNTANSI TERHADAP PRESTASI BELAJAR MAHASISWA JURUSAN AKUNTANSI (STUDI PADA UNIVERSITAS SAM RATULANGI) - Wuniarto, Stevi; Manossoh, Hendrik; Mawikere, Lidia M. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Achievement in learning is the result of the learning process that is determined by students individually in a certain time frame. The results of learning achievement are different for everyone, and are recorded as a score in your report card or in the achievement index. Learning achievement of a person is influenced by two factors, internal (from the individual) and external (outside of the individual), where the individual factor is more influential that the external factor, so the writer of this research have decided to emphasized more on the internal factors which are the self concept and self efficacy. The purpose of this research is to determine the influence of self concept and self efficacy on Majoring Accounting student towards their learning achievements. This research uses the survey method to collect prime data from a population of Majoring Accounting student from the University of Sam Ratulangi and also uses the determination of sample based on purposive sampling method. This research uses multiple linear regression analysis tools with the help of SPSS 22. The result of the research are, (1) Self concept has a significant influence on student learning achievement, (2) Self efficacy has a significant influence on student study prestige. Keywords: Self Concept, Self Efficacy, Learning Achievement